Psikologi sebagai Landasan Pendidikan: Peran Psikologi Perkembangan dan Psikologi Belajar dalam Meningkatkan Kualitas Pembelajaran - Prihaten Maskhuliah; Aulia Salsabila Putri; Dewi Mawaddah Rumaf; Tita Mustikawati Selayar; Alfaris Syahdan Nurpratama; Iman Bugis; Firanti Nur Hayoto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Psychology plays a vital role as one of the cornerstones of education, as it provides an understanding of learners’ characteristics, development and learning processes. This understanding equips educators to design learning experiences tailored to the needs and potential of each individual. This article aims to examine the importance of developmental psychology and learning psychology as a foundation for creating more effective learning processes. The article was written using a literature review (library research) method, drawing on various academic sources, such as books and journals related to educational psychology. The findings indicate that developmental psychology helps educators understand the stages of learners’ development, enabling learning to be tailored to the characteristics of each developmental phase. On the other hand, learning psychology provides an understanding of the learning process, the factors influencing learning success, and various learning approaches such as behaviourist, humanistic and cognitive approaches which can be applied in accordance with learners’ needs. By understanding these two aspects, educators can determine more appropriate learning strategies, methods and resources, thereby creating a conducive learning environment, boosting motivation to learn, and supporting the achievement of optimal learning outcomes. Thus, psychology serves as a vital foundation for realising learner-centred, humanistic learning that supports the achievement of educational objectives in their entirety.